Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's solve the equation [tex]\(\sqrt{x + 9} - x = 9\)[/tex] step-by-step and verify the solutions.
1. Start with the given equation:
[tex]\[ \sqrt{x + 9} - x = 9 \][/tex]
2. Isolate the square root on one side of the equation:
[tex]\[ \sqrt{x + 9} = x + 9 \][/tex]
3. Square both sides of the equation to eliminate the square root:
[tex]\[ (\sqrt{x + 9})^2 = (x + 9)^2 \][/tex]
4. Simplify both sides:
[tex]\[ x + 9 = (x + 9)^2 \][/tex]
5. Expand the right side of the equation:
[tex]\[ x + 9 = x^2 + 18x + 81 \][/tex]
6. Bring all terms to one side to set the equation to zero:
[tex]\[ 0 = x^2 + 18x + 81 - x - 9 \][/tex]
7. Simplify the equation:
[tex]\[ 0 = x^2 + 17x + 72 \][/tex]
8. Solve the quadratic equation [tex]\(x^2 + 17x + 72 = 0\)[/tex].
The quadratic formula is given by [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex]. Here, [tex]\(a = 1\)[/tex], [tex]\(b = 17\)[/tex], and [tex]\(c = 72\)[/tex].
[tex]\[ x = \frac{-17 \pm \sqrt{17^2 - 4 \cdot 1 \cdot 72}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{289 - 288}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{1}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm 1}{2} \][/tex]
Therefore, the solutions are:
[tex]\[ x = \frac{-17 + 1}{2} = \frac{-16}{2} = -8 \][/tex]
and
[tex]\[ x = \frac{-17 - 1}{2} = \frac{-18}{2} = -9 \][/tex]
9. Verify the solutions:
- For [tex]\(x = -8\)[/tex]:
[tex]\[ \sqrt{-8 + 9} - (-8) = \sqrt{1} + 8 = 1 + 8 = 9 \][/tex]
This is true.
- For [tex]\(x = -9\)[/tex]:
[tex]\[ \sqrt{-9 + 9} - (-9) = \sqrt{0} + 9 = 0 + 9 = 9 \][/tex]
This is also true.
Thus, the solutions to the equation [tex]\(\sqrt{x + 9} - x = 9\)[/tex] are [tex]\(\boxed{-9}\)[/tex] and [tex]\(\boxed{-8}\)[/tex].
1. Start with the given equation:
[tex]\[ \sqrt{x + 9} - x = 9 \][/tex]
2. Isolate the square root on one side of the equation:
[tex]\[ \sqrt{x + 9} = x + 9 \][/tex]
3. Square both sides of the equation to eliminate the square root:
[tex]\[ (\sqrt{x + 9})^2 = (x + 9)^2 \][/tex]
4. Simplify both sides:
[tex]\[ x + 9 = (x + 9)^2 \][/tex]
5. Expand the right side of the equation:
[tex]\[ x + 9 = x^2 + 18x + 81 \][/tex]
6. Bring all terms to one side to set the equation to zero:
[tex]\[ 0 = x^2 + 18x + 81 - x - 9 \][/tex]
7. Simplify the equation:
[tex]\[ 0 = x^2 + 17x + 72 \][/tex]
8. Solve the quadratic equation [tex]\(x^2 + 17x + 72 = 0\)[/tex].
The quadratic formula is given by [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex]. Here, [tex]\(a = 1\)[/tex], [tex]\(b = 17\)[/tex], and [tex]\(c = 72\)[/tex].
[tex]\[ x = \frac{-17 \pm \sqrt{17^2 - 4 \cdot 1 \cdot 72}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{289 - 288}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{1}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm 1}{2} \][/tex]
Therefore, the solutions are:
[tex]\[ x = \frac{-17 + 1}{2} = \frac{-16}{2} = -8 \][/tex]
and
[tex]\[ x = \frac{-17 - 1}{2} = \frac{-18}{2} = -9 \][/tex]
9. Verify the solutions:
- For [tex]\(x = -8\)[/tex]:
[tex]\[ \sqrt{-8 + 9} - (-8) = \sqrt{1} + 8 = 1 + 8 = 9 \][/tex]
This is true.
- For [tex]\(x = -9\)[/tex]:
[tex]\[ \sqrt{-9 + 9} - (-9) = \sqrt{0} + 9 = 0 + 9 = 9 \][/tex]
This is also true.
Thus, the solutions to the equation [tex]\(\sqrt{x + 9} - x = 9\)[/tex] are [tex]\(\boxed{-9}\)[/tex] and [tex]\(\boxed{-8}\)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.